Pengaruh Viral Marketing, Celebrity Endorser, Dan Brand Image Terhadap Keputusan Pembelian Produk Skincare Skintific - Habib Hakim; Senjaya Senjaya; Erina Santo; M. Tahir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research is motivated by the aim to determine and analyze the influence of Viral Marketing, Celebrity Endorser, and Brand Image on the purchase decision of Skintific Skincare products. This research approach is based on a quantitative approach. The sample was 97 respondents using Simple random sampling as a sampling technique. Test results that partially and simultaneously Viral Marketing, Celebrity Endorser, and Brand Image have a positive and significant effect on the purchase decision of Skintific Skincare products.